Life in a Silken Net: Mourning the Beloved Monstrous in Lydie Breeze - Gross, Robert F. (Journal of Dramatic Theory and Criticism, 1994)
Life in a Silken Net: Mourning the Beloved Monstrous in Lydie Breeze